(untitled) (International Journal of Engineering and Computer Science, 2017)
As demand for sharing and accessing files online is increasing, people are likely to shift their focus from traditional file sharing systems to online file sharing system so that files could be accessed any time and any place. Variety of file sharing applications is available to ease sharing files online. In this paper, we are presenting a file sharing system which is devoted to sharing and accessing files in an organization. Requirements of sharing files for an organization are a bit different from general file sharing applications that are available. This web application will be an interactive application for organization wherein ideas can also be shared along with file sharing and users will be provided with different privileges to share file which is currently not present in available file sharing applications